Hak Konstitusional Korban atas Pengadilan HAM yang Kompeten, Independen, dan Imparsial - Yustina Trihoni Nalesti Dewi (Jurnal Konstitusi, 2016)
Court of Human Rights, guarantee a fair trial for the sake of protecting human and human dignity must be realized in line with the principles of the Indonesian nation berketuhanan and equitable. The establishment of a Human Rights Court will be the initial parameters that indicate to what extent the seriousness of the Government of the Republic of Indonesia to protect and promote human rights as mandated by the Pancasila as Cita Law (Rechtsidee). Court of Human Rights also  be a stepping stone towards the reform of the legal system in Indonesia. Guarantees the right to a fair trial under Article 28 D (1) of the Constitution of 1945, which  then further elaborated by Article 24 of the 1945 Constitution of the judicial power. However, what was before the law and According to the law is not necessarily so in fact before the court and According to the court. Empirical experience shows the benefit of victims in court human rights are often violated because of various political interests. In order to maintain accountability of the judicial process at the Human Rights Court, need community involvement as a control in order to increase awareness of the implementation of a fair trial. It is very important is the guarantee of public trials that are part of a fair trial with the aim of protecting the interests of the accused or the victim of the confidentiality of a hearing in the absence of public  scrutiny.